Growth of microscale In2O3 islands on Y-stabilized zirconia(100) by molecular beam epitaxy - Bourlange, A; Payne, D; Jacobs, R; Egdell, R; Foord, J; Schertel, A; Dobson, P; Hutchison, J (2008)
The growth of micrometer sized arrays of InO islands on Y-stabilized ZrO(100) was investigated. Indium oxide layers were grown on Y-stabilized ZrO(100) substrates in a UHV oxide MBE system with a base pressure of 5 × 10 mbar and incorporating an indium Knudsen cell and a radiofrequency oxygen plasma source. Substrates were cleaned by exposure to the oxygen atom beam at a substrate temperature of 900 °C. Films were then grown to an estimated thickness of 120 nm with a deposition rate of 0.04 nm/s at a substrate temperature of 900 °C. The epitaxial relationship between the InO islands and the substrate is confirmed by selected area electron diffraction carried out in the HRTEM. It was observed that Y-stabilized ZrO is a versatile substrate whose lattice parameter varies with Y doping level, thus providing a means of varying the mismatch with InO epilayers.